Clinical, functional and inflammatory characteristics in patients with paucigranulocytic stable asthma: Comparison with different sputum phenotypes. Issue 11 (11th May 2017) - Ntontsi, P.; Loukides, S.; Bakakos, P.; Kostikas, K.; Papatheodorou, G.; Papathanassiou, E.; Hillas, G.; Koulouris, N.; Papiris, S.; Papaioannou, A. I.
Abstract: Background: According to induced sputum cell count, four different asthma phenotypes have been recognized (eosinophilic, neutrophilic, mixed and paucigranulocytic). The aim of this study was to detect functional and inflammatory characteristics of patients with paucigranulocytic asthma. Methods: A total of 240 asthmatic patients were categorized into the four phenotypes according to cell counts in induced sputum. All patients underwent pulmonary function tests, and measurement of fraction of exhaled nitric oxide (FeNO). The levels of IL‐8, IL‐13 and eosinophilic cationic protein (ECP) were also measured in sputum supernatant. Treatment, asthma control and the presence of severe refractory asthma (SRA) were also recorded. Results: Patients were categorized into the four phenotypes as follows: eosinophilic (40%), mixed (6.7%), neutrophilic (5.4%) and paucigranulocytic (47.9%). Although asthma control test did not differ between groups ( P =.288), patients with paucigranulocytic asthma had better lung function (FEV1 % pred) [median (IQR): 71.5 (59.0‐88.75) vs 69.0 (59.0‐77.6) vs 68.0 (60.0‐85.5) vs 80.5 (69.7‐95.0), P =.009] for eosinophilic, mixed, neutrophilic and paucigranulocytic asthma, respectively, P =.009). SRA occurred more frequently in the eosinophilic and mixed phenotype (41.6% and 43.7%, respectively) and less frequently in the neutrophilic and paucigranulocytic phenotype (25% and 21.7%, respectively, P =.01). FeNO, ECP and IL‐8 were all low in the paucigranulocytic, whereas as expected FeNO and ECP were higher in eosinophilic and mixed asthma, while IL‐8 was higher in patients with neutrophilic and mixed asthma ( P <.001 for all comparisons). Interestingly, 14.8% of patients with paucigranulocytic asthma had poor asthma control. Conclusion: Paucigranulocytic asthma most likely represents a "benign" asthma phenotype, related to a good response to treatment, rather than a "true" phenotype of asthma. However, paucigranulocytic patients that remain not well controlled despite optimal treatment represent an asthmatic population that requires further study for potential novel targeted interventions.